Budaya Religius dalam Membentuk Karakter Peserta Didik di MTS Sullamul Istiqomah Bekasi - Vanny Amanda Fadillah; Anas Fauzi; Idham (JPNM Jurnal Pustaka Nusantara Multidisiplin, 2025)
This research is motivated by the importance of shaping students’ religious character within the school environment through the habituation of Islamic values in daily life. The main problem addressed in this study is the decline of students’ moral values due to external environmental influences and the lack of consistency among some students in participating in religious activities programmed by the school. This study employs a qualitative approach with a case study method. Data were collected through observation, interviews with 1 principal, 2 teachers, and 2 students, as well as documentation from various sources. The research procedures included planning, implementation, and analysis of supporting and inhibiting factors in the application of religious culture in the school. The results of the study show that the implementation of religious culture at MTs Sullamul Istiqomah Bekasi has been in accordance with the theory of planning and implementation of religious culture, which includes: 1) Religious culture is designed through programs such as Qur’an recitation, congregational prayers, muhadharah, Qiroati, and Qur’an Workshop. 2) The activities are carried out routinely and integrated into the daily life of the school. 3) Supporting factors include the commitment of the leadership, teacher involvement, facilities, and parental support, while the main inhibiting factors are external environmental influences and students’ diverse backgrounds. Religious culture has proven to be effective in shaping students’ religious character, discipline, and sense of responsibility.